Exposure of formal and informal nail technicians to organic solvents found in nail products - Keretetse, Goitsemang; Nelson, Gill; Brouwer, Derk (Frontiers in Public Health, 2023)
Nail technicians are exposed to volatile organic compounds (VOCs) emitted from nail products used in their daily work, which may cause adverse health effects. This study aimed to assess VOC exposure of nail technicians in the South African formal and informal sectors and to provide a task-based exposure assessment of different nail applications. Personal passive sampling was conducted on 10 formal and 10 informal nail technicians located in the northern suburbs of Johannesburg and the Braamfontein area, over three days. Real-time measurements were taken to determine task-based peak exposures. The number of clients serviced, working hours, type of nail application, type of ventilation, room volume, and carbon dioxide (CO2) concentrations, were also recorded. There were differences in the nail products used, the types of nail applications performed, the number of clients serviced, and breathing zones VOC concentrations of the formal and informal nail technicians. Some formal nail salons were equipped with mechanical ventilation while the informal nail salons relied on natural ventilation. CO2 concentrations were higher in the informal than the formal nail salons and increased during the course of the working day. Formal nail technicians were exposed to higher total volatile organic compounds (TVOC) concentrations than informal nail technicians, which may be due to the different nail application procedures as well as ‘background’ emissions from their co-workers - the bystander effect. Acetone was the predominantly detected VOC: the formal nail technicians were exposed to significantly higher TWA (8h) concentrations (geometric mean (GM) 43.8 ppm, geometric standard deviation (GSD) 2.49) than were the informal nail technicians (GM 9.87 ppm, GSD 5.13). Methyl methacrylate among the informal nail technicians was measured at 89.7% detection frequency, far higher than that among the formal nail technicians (3.4%). This may be attributed to the observed popularity of acrylic nail applications in this sector. Nail applications involving soak-off gave rise to high TVOC peaks at the start of the nail application process. This is the first study to compare organic solvent exposures among formal and informal nail technicians and determine task-based peak exposures. It also brings attention to the often-overlooked informal sector of this industry.